A structural optimization of laminated composite curved structure for an elastic shock absorber of UAV based on a novel theory. Issue 15 (7th June 2022) - Kim, Yongha; Lee, Jungjin; Park, Jungsun
Abstract: This article defines a theoretical method to the progressive failure analysis of a laminated composite curved structure for an elastic shock absorber of a UAV (Unmanned Aerial Vehicle). Based on the continuous model, the theoretical method is presented for purposes of investigating the material failure and post-failure behavior of the laminated composite curved structure. This method is derived using the Ritz method and Hashin's failure criteria. The validity of the theoretical method is verified by comparing the results of the finite element analysis. Finally, the theoretical method is applied to optimizing a laminated composite curved structure for an elastic shock absorber of a UAV to minimize the mass and maximize the shock absorption performance. Furthermore, the shock absorption performance of the optimized elastic shock absorber is confirmed by the finite element analysis (3D explicit dynamic analysis). The optimization result allows a database to be obtained on the structural characteristics of laminated composite curved structure for aerospace applications. Consequently, it is concluded that the theoretical method is well suited to the progressive failure analysis of a laminated composite curved structure for aerospace applications due to their relative simplicity and computational efficiency.